Methyl Jasmonate Protects the PS II System by Maintaining the Stability of Chloroplast D1 Protein and Accelerating Enzymatic Antioxidants in Heat-Stressed Wheat Plants - Mehar Fatma; Noushina Iqbal; Zebus Sehar; Mohammed Nasser Alyemeni; Prashant Kaushik; Nafees A. Khan; Parvaiz Ahmad (MDPI AG, 2021)
The application of 10 µM methyl jasmonate (MeJA) for the protection of wheat (Triticum aestivum L.) photosystem II (PS II) against heat stress (HS) was studied. Heat stress was induced at 42 °C to established plants, which were then recovered at 25 °C and monitored during their growth for the study duration. Application of MeJA resulted in increased enzymatic antioxidant activity that reduced the content of hydrogen peroxide (H2O2) and thiobarbituric acid reactive substances (TBARS) and enhanced the photosynthetic efficiency. Exogenous MeJA had a beneficial effect on chlorophyll fluorescence under HS and enhanced the pigment system (PS) II system, as observed in a JIP-test, a new tool for chlorophyll fluorescence induction curve. Exogenous MeJA improved the quantum yield of electron transport (ETo/CS) as well as electron transport flux for each reaction center (ET0/RC). However, the specific energy fluxes per reaction center (RC), i.e., TR0/RC (trapping) and DI0/RC (dissipation), were reduced by MeJA. These results indicate that MeJA affects the efficiency of PS II by stabilizing the D1 protein, increasing its abundance, and enhancing the expression of the psbA and psbB genes under HS, which encode proteins of the PS II core RC complex. Thus, MeJA is a potential tool to protect PS II and D1 protein in wheat plants under HS and to accelerate the recovery of the photosynthetic capacity.